Periodontal disease in patients with type 2 Diabetes mellitus - Obradović Radmila R.; Kesić Ljiljana G.; Pejčić Ana S.; Igić Marija Lj; Bojović Marija D.; Stanišić Dragana N.; Petrović Milica S.; Stanković Ivana V.; Jovanović Marija G. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2018)
Diabetes mellitus (DM) is one of the most prevalent endocrine metabolic disorders. It has damaging effects on the oral cavity and is reported to be a risk factor for periodontal disease. The aim of the study was to describe the periodontal status of patients with type 2 DM and to evaluate the multiple demographic, behavioral, medical and dental factors that may be associated with periodontal disease and DM. Material and Methods: Demographic data and medical and dental histories were reviewed, periodontal assessments (loss of attachment, bleeding on probing, presence of supragingival calculus) and cytomorphometric analysis were made. Results: 160 subjects participated in the study, age of 64.2 (±0.2) years, duration of DM 23.6 (±0.39) years and HbA1c 8.70% (±0.45). Severe loss of attachment and calculus were more present in older patients. Bleeding on probing was consistent among subjects in each age group. Cytomorphometric analysis revealed larger nuclear area values in older subjects. Factors possibly associated with advanced periodontal disease included in the regression analysis were: age (P<0.001), current smoking cigarettes (p<0.001), having ever smoked cigarettes (p<0.001), tooth brushing (p=0.017), visits to the dentist (p=0.068), duration of disease (p=0.034), xerostomia (p=0.500), HbA1c(p=0.119), neuropathy (p=0.017), nephropathy (p=0.389), retinopathy (p=0.5 50) and peripheral vascular disease (p=0.060). Conclusion: Periodontal disease was common in adult diabetic population. Cigarette smoking and older age were associated with a higher prevalence of advanced periodontal disease. Smoker-diabetic patients are at high risk for poor periodontal prognosis, and they should be included in regular periodontal control check up and treatment.